2020
DOI: 10.1002/jcph.1680
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Quizartinib in Healthy Volunteers and Patients With Relapsed/Refractory Acute Myeloid Leukemia

Abstract: Quizartinib is an FMS-like tyrosine kinase 3 (FLT3) inhibitor that has shown robust clinical activity in patients with FLT3-internal tandem duplicationmutated relapsed/refractory acute myeloid leukemia (AML). This analysis evaluated the population pharmacokinetics (PK) of quizartinib and its active metabolite, AC886, in a pooled analysis of data from 649 healthy volunteers or patients with AML from 8 clinical trials including the phase 3 QuANTUM-R study. Quizartinib was given as a single dose or multiple once-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the drug–drug interaction study, the quizartinib steady-state AUC and C max were predicted to increase by 96% and 86%, respectively, with concomitant administration of the strong CYP3A inhibitor ketoconazole [ 9 ]. In the population PK analysis, quizartinib AUC increased by 82% and C max increased by 72% with concomitant use of a strong CYP3A inhibitor [ 13 ]. Because the current analysis demonstrated a positive exposure–response relationship in C–QTc, these results suggest that dose reduction is necessary for patients who are receiving a concomitant strong CYP3A inhibitor to minimize the risk of QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the drug–drug interaction study, the quizartinib steady-state AUC and C max were predicted to increase by 96% and 86%, respectively, with concomitant administration of the strong CYP3A inhibitor ketoconazole [ 9 ]. In the population PK analysis, quizartinib AUC increased by 82% and C max increased by 72% with concomitant use of a strong CYP3A inhibitor [ 13 ]. Because the current analysis demonstrated a positive exposure–response relationship in C–QTc, these results suggest that dose reduction is necessary for patients who are receiving a concomitant strong CYP3A inhibitor to minimize the risk of QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…The final C–QTc model was utilized to obtain the model-predicted mean ΔQTcF and 90% confidence interval (CI) at the maximum concentration at steady state ( C max,ss ). Individual C max,ss values for patients enrolled in QuANTUM-R who received quizartinib 60 mg were generated using the population PK model [ 13 ], then the geometric mean of quizartinib C max,ss was obtained. When making predictions of ΔQTcF, the bootstrap method was used to account for multiple parameters in the model and the correlation between the parameters [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…17 The effect of strong CYP3A inhibitors on quizartinib exposure has also been reported in a population PK analysis. 18 An open-label, randomized, parallel-group study in healthy volunteers showed minimal effects of lansoprazole on the plasma concentrations of quizartinib and AC886. 19 A Phase 1 dose-escalation study was conducted in 19 patients with newly diagnosed AML (9 patients were FLT3-ITD positive) in the United States (NCT01390337).…”
mentioning
confidence: 99%
“…14 The pharmacokinetic (PK) and drug-drug interaction profiles of quizartinib have been investigated in several studies. [15][16][17][18][19] Coadministration of cytochrome P450 (CYP) 3A inhibitors (ketoconazole or fluconazole) with quizartinib increased the area under the plasma concentration-time curve (AUC) and maximum plasma concentration (C max ) of quizartinib, especially with ketoconazole. The half-life was ex-tended, but the time to reach maximum plasma concentration (t max ) remained unchanged, except for AC886 when quizartinib was coadministered with ketoconazole.…”
mentioning
confidence: 99%
See 1 more Smart Citation